A very short O—H⋯O hydrogen bond in the structure of clozapinium hydrogen bis(3,5-dinitrobenzoate) - Shaibah, Mohammed A. E. (Acta Crystallogr E Crystallogr Commun, 2020)
In the title salt {systematic name: 4-[6-chloro-2,9-diazatricyclo[9.4.0.0(3,8)]pentadeca-1(15),3(8),4,6,9,11,13-heptaen-10-yl]-1-methylpiperazin-1-ium 3,5-dinitrobenzoate–3,5-dinitrobenzic acid (1/1)}, C(18)H(20)ClN(4) (+)·C(7)H(3)N(2)O(6) (−)·C(7)H(4)N(2)O(6), there is a very short, asymmetric, O—H⋯O hydrogen bond [O⋯O = 2.453 (3) Å] within the anion. The oxygen atoms of one of the nitro groups of the anion are disordered over two sets of sites having occupancies of 0.56 (3) and 0.44 (3). The fused tricyclic portion of the cation adopts a butterfly conformation, with a dihedral angle of 45.59 (6)° between the planes of the two aryl rings. In the crystal, a combination of O—H⋯O, N—H⋯O and C—H⋯O hydrogen bonds links the component species into a three-dimensional framework. Comparisons are made with the structures of some related compounds.